Pengaruh Kesadaran Merek dan Citra Merek terhadap Minat Beli Konsumen Toko SRC di Kabupaten Sleman - Damanik, Fransius Awaldo (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
This study examines the impact of brand awareness and brand image on consumers' purchase intentions. SRC, a modern grocery store participating in the PT SRC Indonesia Sembilan (SRCIS) partnership program, aims to enhance the competitiveness of MSME grocery stores through business support and sustainability initiatives. The research employs multiple linear regression analysis, preceded by descriptive analysis and traditional assumption tests. The significance score of 0.008 reveals a positive and significant influence of brand awareness on consumers' purchase intentions at the SRC shop in Sleman Regency. A positive correlation exists between brand recognition and increased buying interest. Additionally, with a significance score of 0.000, brand image is shown to have a significant and favorable effect on consumers' purchase intentions at the SRC shop. A positive brand image leads to a proportional increase in consumers' purchase intentions. Overall, brand awareness and brand image together account for 55.7% of the influence on consumers' propensity to purchase at the SRC shop in Sleman Regency.